Activation of MET signaling by HDAC6 offers a rationale for a novel ricolinostat and crizotinib combinatorial therapeutic strategy in diffuse large B‐cell lymphoma. Issue 2 (20th August 2018) - Liu, Zebing; Cai, Ying; Yang, Yu; Li, Anqi; Bi, Rui; Wang, Lisha; Shen, Xiaohan; Wang, Weige; Jia, Yijun; Yu, Baohua; Cao, Bing; Cui, Wenli; et al.
Abstract: Some histone deacetylases (HDACs) promote tumor cell growth and pan‐ or selective HDAC inhibitors are active in some cancers; however, the pivotal HDAC enzyme and its functions in human diffuse large B‐cell lymphoma (DLBCL) remain largely unknown. Using NanoString nCounter assays, we profiled HDAC mRNA expression and identified HDAC6 as an upregulated HDAC family member in DLBCL tissue samples. We then found that HDAC6 plays an oncogenic role in DLBCL, as evidenced by its promotion of cell proliferation in vitro and tumor xenograft growth in vivo . Mechanistically, the interaction between HDAC6 and HR23B downregulated HR23B expression, thereby reducing the levels of casitas B‐lineage lymphoma (c‐Cbl), an E3 ubiquitin ligase for hepatocyte growth factor receptor (MET), which resulted in the inhibition of MET ubiquitination‐dependent degradation. In addition, enhanced HDAC6 expression and decreased HR23B expression were correlated with poor overall survival rates among patients with DLBCL. Taken together, these results establish an HDAC6–HR23B–MET axis and indicate that HDAC6 is a potent promoter of lymphomagenesis in DLBCL. Thus, a therapeutic strategy based on HDAC6 inhibitors in combination with MET inhibitors is promising. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.